Major Driving Forces for The Indian SME Pharmaceutical Industry: Using Porter’s Five Forces Framework for A Comparative Analysis: Life Sciences - Rathore, Dr.Chitra; Kalita, Dr. Jyoti Prasad; Sharma, Dr. Satish Chand; Tiwari, Sadhana; Agarwal, Dr. Priyanka (International Journal of Life Science and Pharma Research, 2023)
The author aims to study the major driving forces that affect the operational efficiency of the Indian pharmaceutical industry with special reference to the SME pharmaceutical companies in India. For this, Porter’s Five Force Model is used as a frame of reference to gauge the effect of the various environmental and regulatory forces that affect the working of the Indian SME pharmaceutical industry, using Regression Analysis as the main tool. The reliability and the Regression equation derived from the Regression Analysis showed that competitive rivalry among existing firms is the strongest force, followed by the bargaining power of buyers, the threat of new entrants, the bargaining power of suppliers, and the threat of substitute products in that order. Many researchers have studied the Porter model in theory, and others have studied the different aspects of the pharmaceutical industry. However, there needs to be more research on the analysis of the pharma industry using the Porter model, apart from the pioneering work of Michael Dobbs. This study follows in his footprints and applies the Porter model to the Indian pharma industry with special reference to the SME units. The industry will find this research of practical value, especially for SME industries that can use the outcomes of this study to devise their strategies for growth and competition assessment.